Conversion and Assimilation of Dhimmis in the Ottoman Empire: A Case of Manastir with Special Reference to 18th Century Judicial Records - Idriz, Mesut (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Conversion and Assimilation of Dhimmis in the Ottoman Empire: A Case of Manastir with Special Reference to 18th Century Judicial Records